Positive and Negative Lessons from Hidden Curriculum at a Philippine State University - Louie Giray, Ma. Kasandra Christina Asuncion, Jelomil Edem, Daxjhed Louis Gumalin, Jomarie Jacob, Sheila May Lucero (Educational Process: International Journal)
Background/purpose – Little attention is placed upon the lesser-known form of academic curriculum–that is, the hidden curriculum–and most especially in the Philippine context. This study explored the positive and negative lessons from hidden curricula in the higher education context, with a Philippine state university as the research setting.